Penilaian Sistematis Kualitas Aplikasi Smartphone Tumbuh Kembang Anak - Vernanda, Dwi (Jurnal PROCESSOR, 2023)
Currently there are 38 smartphone applications for parents in monitoring the growth and development of children (toddlers) on the Google Playstore, but until now there has not been a single application recommendation that parents must install and there has been no systematic assessment of application quality during use. Of the 38 applications, a selection was made using several criteria and 11 applications met the criteria for further evaluation. This study aims to assess the quality of children’s growth and development applications (falling) objectively with the method used, namely the Mobile Application Rating Scale (MARS) which has been validated with 5 subscales namely involvement, functionality, aesthetics, information, and subjective quality. The relationship between overall application quality and user ratings and the number of downloads was evaluated by three assessors, namely application users for more than one year, ordinary users who have just downloaded the application, and coders (parties from the puskesmas). The results of the research from 11 applications that meet the criteria, the average MARS score of the application is 3.5. Although there are many smartphone applications that parents can download, there are three recommended applications, namely About Children. My Prima, and Pregnant Friends. The About Children application has the highest MARS score of 4.36, this application has received a perfect rating of 5.0 since it was officially developed in 2017. The About Children application has been downloaded more than 500 thousand and was developed jointly with the Ministry of Health, the Ministry of Education and Culture, and also the BKKBN.